2012
DOI: 10.1111/j.1439-0426.2012.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Species composition of benthic fish fauna in the Sea of M armara, T urkey

Abstract: Summary In order to determine the present benthic fish fauna in the Sea of Marmara, sampling was conducted at a total of 10 stations for 2 weeks in August 2009, using a commercial twin beam trawling vessel with 18 and 36 mm stretched mesh sizes at the cod‐end. In addition, some physicochemical parameters that play important roles, such as temperature, salinity, dissolved oxygen, and pH, were measured for each station. As a result, 31 fish species from 23 families were found at a total of 10 stations in depths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Torcu Koç et al (2012) described 31 fish species using a beam trawl from 10 stations in the Sea of Marmara. The lower species richness in the study of Torcu Koç et al (2012) may be due to the limited operational depth range of beam trawls. However, in the present study, higher teleost fish species richness was found with increasing depth.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Torcu Koç et al (2012) described 31 fish species using a beam trawl from 10 stations in the Sea of Marmara. The lower species richness in the study of Torcu Koç et al (2012) may be due to the limited operational depth range of beam trawls. However, in the present study, higher teleost fish species richness was found with increasing depth.…”
Section: Discussionmentioning
confidence: 97%
“…Since trawl fisheries is banned in the Sea of Marmara, commercial catches of demersal fish are caught by beam trawls and deep water gill nets. Therefore, information on demersal fish composition and spatial and temporal variations are limited (Gözenç et al, 1997;Eryılmaz, 2001;Torcu-Koç et al, 2012;Keskin et al, 2011). Beside, Eryılmaz and Meriç (2005), and Demirel and Gül (2016) were reviewed historical and earliear demersal fish records from the Sea of Marmara.…”
Section: Introductionmentioning
confidence: 99%
“…The Sea of Marmara comprises two different water masses from two different seas. Black Sea-sourced upper water masses vary between 50 and 75 m in thickness depending on the amount of incoming water from the Black Sea; water temperatures, especially seasonally, are between 6 o Cand 27 o C. Living organisms in the Sea of Marmara are not easily influenced by salinity variations, which can be in accordance with hypersaline waters of the Mediterranean Sea (35-39%o) and hyposaline waters of the Black Sea (16-18%o).But, as thermoklin stagnation arising from variations in temperature and salinity changes the chemical structure of the Sea of Marmara, ecological conditions of the sea vary at the same time (Karakulak et al 2000, Torcu et al 2012. As the southern Marmara in which Bandırma Bay placed is relatively larger and deeper, with open sea, and thefore, its structure possibly supplies a greater diversity of fish communities as T. Mediterraneus.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, C. linguatula keeps oneself a lot of from the polluted area (Northeastern part). Torcu Koç et al, (2012) were determined that 4.49% of the total demersal fish biomass of the Marmara Sea consisted of C. linguatula. In this study, C. linguatula constituted 0.1% of the total biomass.…”
Section: Discussionmentioning
confidence: 99%